2023
DOI: 10.3390/polym15112442
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of CuO-NP-Doped PVDF Composites Based Electrospun Triboelectric Nanogenerators for Wearable and Biomedical Applications

Abstract: A flexible and portable triboelectric nanogenerator (TENG) based on electrospun polyvinylidene fluoride (PVDF) doped with copper oxide (CuO) nanoparticles (NPs, 2, 4, 6, 8, and 10 wt.-% w.r.t. PVDF content) was fabricated. The structural and crystalline properties of the as-prepared PVDF-CuO composite membranes were characterized using SEM, FTIR, and XRD. To fabricate the TENG device, the PVDF-CuO was considered a tribo-negative film and the polyurethane (PU) a counter-positive film. The output voltage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 102 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…The sensor utilized in this research helps to produce electricity by contact with bodily movements and can successfully detect heartbeat and respiration by placing the sensor in both supine and prone positions as depicted in Figure 16a−d. Amrutha et al 18 successfully fabricated a portable electrospun PVDF composite fiber-based TENG for biomedical applications. The properties of the PVDF fiber were enhanced by the doping of various ratios of CuO NPs (2, 4, 6, 8, and 10 wt %).…”
Section: Body Motion Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensor utilized in this research helps to produce electricity by contact with bodily movements and can successfully detect heartbeat and respiration by placing the sensor in both supine and prone positions as depicted in Figure 16a−d. Amrutha et al 18 successfully fabricated a portable electrospun PVDF composite fiber-based TENG for biomedical applications. The properties of the PVDF fiber were enhanced by the doping of various ratios of CuO NPs (2, 4, 6, 8, and 10 wt %).…”
Section: Body Motion Sensorsmentioning
confidence: 99%
“…(e) Body movements dictated by placing TENG in (i) tapping, (ii) elbow, (iii) pocket, (iv) leg, (v) chair, (vi) shoe, and (vii) heartbeat monitoring by placing the sensor in the prone position. Reproduced with permission from ref . Copyright 202, MDPI.…”
Section: Applications Of Tengsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our research group, a similar kind of work has been reported for PVDF-aromatic hyperbranched polymer/TPU-and CuO-PVDF/TPU-based TENGs. 43,55 A detailed comparison of the electrical output generated by the proposed TENG with that of a previously reported energy harvesting device is presented in Table S1 (SI).…”
Section: Introductionmentioning
confidence: 99%
“…The net dipole moment exhibited by the β-phase is 8 × 10 –30 C·m per unit cell. Moreover, the β-phase of PVDF plays the most pivotal role in enhancing the electrical output of the fabricated TENGs. , Currently, the betterment of PVDF dielectric characteristics and most electroactive β-phase have been explored by incorporating or doping different nanofillers such as Ag NWsx, CuO NPs, NiO NPs, , BaTiO 3 , graphene oxide, and sepiolite (an inorganic nanoclay) . Out of these, NiO NPs are the most significant nanofillers to dope into the PVDF matrix because they have the ability to modify the mechanical, electrical (band gap 3.6–4 eV), and magnetic properties without affecting the flexibility of the nanofiber mats. , Numerous methods have been published in the literature for NiO NP synthesis, including ultrasonication, sol–gel, coprecipitation, and microwave pyrolysis.…”
Section: Introductionmentioning
confidence: 99%